TANGGUNG JAWAB PENGGUNAAN DATA PRIBADI OLEH PENYELENGGARA SISTEM ELEKTRONIK DALAM LAYANAN PINJAMAN ONLINE: Responsibility for the Use of Personal Data by Electronic System Operators in Online Lending Services - Yuga, Reinhaldy Ivancka; Hummerson, Andi Widiatno (Faculty of Law, Universitas Trisakti, 2025)
In this era of rapidly developing digital life, the use of information technology has become commonplace. One such development is the emergence of online lending services. These services use electronic systems to conduct their business, including the use of consumers' personal data. Online lending providers that utilize electronic systems are also classified as electronic system operators. In practice, crimes related to personal data, particularly in the online lending sector, are rampant. The responsibility of electronic system operators regarding the use of personal data includes ensuring that their systems are reliable, secure, and responsible for system operations, having a legitimate and clear basis for data processing, providing complete information to the personal data subjects, and maintaining the confidentiality and security of their consumers' data by implementing personal data protection principles. Failure to fulfill the obligations of electronic system operators may result in administrative sanctions, such as written warnings, temporary suspension of activities, deletion of personal data, restriction of products/services, freezing of products/services, dismissal of management, administrative fines, revocation of product licenses, and revocation of business licenses.